Comparing sport education pedagogy in rural and urban schools: A qualitative approach - Díaz Tejerina, David; Lafuente Fernández, Jorge Carlos; Coto Lousas, José Amador; Fernández Río, Francisco Javier (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The aim of this study was to observe whether there are differences between urban and rural school environments when applying an intervention based on the pedagogical model of sports education. A group of 26 sixth-grade students (15 from urban schools and 11 from rural schools) participated. After the analysis of the open questions that were proposed to the participating students, the transfer of the activity outside the classroom and the similarity to a formal season in professional sports were observed as positive aspects in the urban school. Affiliation and competitiveness were the negative aspects, and competitiveness were the most important elements of the intervention. In the rural school, affiliation and help from older classmates were observed as positive aspects. As negative aspects, the weather and competitiveness, and as the most significant elements the novelty and the possibility of building their own material and being able to use it outside the school. It was concluded that the social relationships experienced by students in rural schools are more positive than in urban schools and that the intervention is shown to be an effective strategy in both school environments.